A putative Chondroprotective role for IL-1β and MPO in herbal treatment of experimental osteoarthritis - Nora M. Aborehab; Mahitab H. El Bishbishy; Abeer Refaiy; Nermien E. Waly (BMC, 2017)
Abstract Background Herbal treatment may have a chondroprotective and therapeutic effect on Osteoarthritis (OA). We investigated the mechanism of action of ginger and curcumin rhizomes cultivated in Egypt in treatment of OA in rat model. Methods Thirty-five albino rats were intra-articularly injected with Monosodium Iodoacetate in the knee joint. Ginger and curcumin was orally administered at doses of 200 and 400 mg/kg (F200 and F400). Serum levels of cartilage oligomeric matrix protein (COMP), hyaluronic acid (HA), malondialdehyde (MDA), myeloperoxidase (MPO), Interleukin-1 beta (IL-1β) and superoxide dismutase activity (SOD) were measured using ELISA. The composition of the herbal formula hydro-ethanolic extract was characterized using UPLC-ESI-MS. Histopathological changes in injected joints was examined using routine histopathology. Statistical analysis was performed using one-way ANOVA. Results Serum levels of COMP, HA, MPO, MDA, and IL-1β were significantly decreased in F 200, F 400 and V groups when compared to OA group (P value <0.0001). On the other hand SOD levels were significantly elevated in treated groups compared to OA groups (P value <0.0001). Conclusions The ginger/curcumin at 1:1 had chondroprotective effect via anti-inflammatory and antioxidant effect in rat OA model. Further pharmacological and clinical studies are needed to evaluate this effect.